Influencia de la adición de fibras de pet reciclado sobre la resistencia, cohesión y ángulo de fricción interna de suelos arcillosos aplicado a la estabilidad de taludes - Gil Carbonell, Erick Robinson (2018)
This research presents an alternative for the improvement of the resistance, cohesion and internal friction angle of a clay soil of high plasticity (CH), through the application of the concept of fibro-reinforced soil, in order to increase the factor of safety corresponding to the analysis of slopes’ stability of the theoretical road embankments composed of this type of soil. The soil reinforcement was carried out through random inclusions of recycled polymer fibers of polyethylene terephthalate (PET), which were distributed homogeneously in the soil mass. The geotechnical characterization of the natural soil was realized, sampling of 120 kilograms of clay soil extracted from the right lateral slope located at kilometer 172 of the Trujillo-Huamachuco highway. Subsequently, the compaction test of the Proctor Standard type was realized in order to obtain the parameters of maximum density and optimum water content to be able to carry out the experimental program under these parameters. The variable that was taken into account for the fibro-reinforced soil was the percentage of addition of recycled PET fibers of 20 mm length to 0.3%, 0.6%, 0.9%, 1.2% and 1.5% of the dry weight of the soil, being elaborating a total of 54 cylindrical test pieces, to then evaluate the physical-mechanical performance of the different combinations, by means of the unconsolidated-undrained triaxial compression test UU with confinements of 30, 60 and 120 kPa. From the results of tests, it was found that the percentage of addition of PET fibers improved up to 49.45% the resistance of the soil; likewise, the parameters of cohesion and internal friction angle improved by 22.28% and 72.73% respectively. Through the mathematical analysis with the Bishop Method, it was verified that all percentages of addition of PET fibers represent an increase of the Safety Factor with respect to natural clay soil, with improvement intervals ranging from 3.27% to 24.64%, determining that 0.6% is the optimal percentage of addition. Finally, it was verified that the recycled PET fibers have the potential to improve the stability of road embankment slopes composed of a clay soil, thus presenting a new ecological alternative for the large-scale rejection of waste materials in geotechnical works.